2022
DOI: 10.1177/21650799221081265
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Multilevel Workplace Tobacco Control Interventions: A Scoping Review

Abstract: Background: The workplace provides a unique opportunity to intervene on tobacco use, by implementing multilevel interventions engaging diverse employees. Using the social ecological model (SEM), this scoping review aimed to synthesize descriptions of multilevel workplace tobacco control programs to create a health equity informed framework for intervention planning. Methods: Multiple databases were searched for articles published from January 2010 to December 2020 meeting inclusion criteria (i.e., discussed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our study also calls for encouraging interventions in workplaces (Parkinson et al 2022), especially involving apprenticeship teachers who seem to play an important role with apprentices. As other authors have already suggested, it also confirms the need to encourage family-based smoking education and cessation programs (Legleye et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…Our study also calls for encouraging interventions in workplaces (Parkinson et al 2022), especially involving apprenticeship teachers who seem to play an important role with apprentices. As other authors have already suggested, it also confirms the need to encourage family-based smoking education and cessation programs (Legleye et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…It provides a systematized approach to identifying barriers and facilitators (context of implementation settings), implementation strategies (packages of implementation interventions to address barriers in the context of implementation success), and implementation outcomes (process outcomes of implementation, which indicate implementation success) [14]. To the best of our knowledge, few studies have focused on smoking cessation interventions with an implementation science perspective worldwide, with research being conducted primarily in hospital settings [15][16][17][18][19] and a few in non-hospital settings [20][21][22][23], and no reviews have covered settings such as hospitals, communities, workplaces, and schools. Since the implementation of smoking cessation interventions varies globally, and even within countries despite the existence of global and national tobacco control policies [24], there is a need for studies focusing on implementation in a wide range of settings in a speci c country.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a systematized approach to identifying barriers and facilitators (context of implementation settings), implementation strategies (packages of implementation interventions to address barriers in the context of implementation success), and implementation outcomes (process outcomes of implementation, which indicate implementation success) [13]. To the best of our knowledge, few studies have focused on smoking cessation interventions with an implementation science perspective worldwide, with research being conducted primarily in hospital settings [14][15][16][17][18] and a few in nonhospital settings [19][20][21][22], and no reviews have covered settings such as hospitals, communities, workplaces, and schools. Since the implementation of smoking cessation interventions varies globally, and even within countries despite the existence of global and national tobacco control policies [23], there is a need for studies focusing on implementation in a wide range of settings in a specific country.…”
Section: Introductionmentioning
confidence: 99%